2021
DOI: 10.3390/cancers13020304
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products as Inducers of Non-Canonical Cell Death: A Weapon against Cancer

Abstract: Apoptosis has been considered the main mechanism induced by cancer chemotherapeutic drugs for a long time. This paradigm is currently evolving and changing, as increasing evidence pointed out that antitumor agents could trigger various non-canonical or non-apoptotic cell death types. A considerable number of antitumor drugs derive from natural sources, both in their naturally occurring form or as synthetic derivatives. Therefore, it is not surprising that several natural compounds have been explored for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 270 publications
(180 reference statements)
1
32
0
Order By: Relevance
“…Several signal transduction pathways including iron metabolism, GSH-GPX4, and FSP1-COQ10 constitute the core molecular mechanism of ferroptosis. Increasing evidence has revealed that inducing ferroptosis could act as a promising therapeutic strategy and eliminate the resistance of cancer cells to drug-induced apoptosis [ 27 ]. The mutated RAS family genes are the most common oncogenes in pancreatic cancer that could be selectively targeted by erastin through inducing ferroptosis [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several signal transduction pathways including iron metabolism, GSH-GPX4, and FSP1-COQ10 constitute the core molecular mechanism of ferroptosis. Increasing evidence has revealed that inducing ferroptosis could act as a promising therapeutic strategy and eliminate the resistance of cancer cells to drug-induced apoptosis [ 27 ]. The mutated RAS family genes are the most common oncogenes in pancreatic cancer that could be selectively targeted by erastin through inducing ferroptosis [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that increased autophagy can degrade ferritin and increase iron levels, leading to the Fenton reaction and oxidative damage [ 24 ]. Increasing evidence suggests that induction of ferroptosis is a promising therapeutic strategy for inhibiting cancer cell resistance resulting from drug-induced apoptosis [ 26 ]. Mechanistically, the combination of UA and Cis activates autophagy to degrade the iron storage protein ferritin through a process mediated by the cargo receptor NCOA4.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, HO-1-dependent intracellular Fe 2+ overload induces lipid peroxidation and triggers a noncanonical ferroptosis [ 230 ]. Phytochemicals are often used for this purpose [ 231 ]. Neuroblastoma cell treatment with withaferin A, a steroidal lactone derived from Withania somnifera (Indian ginseng), directly targets Keap1, leading to Nrf2 release and HO-1 up-regulation and consequently increasing intracellular Fe 2+ and inducing ferroptosis [ 232 ].…”
Section: Ho-1 and Tumor Therapiesmentioning
confidence: 99%